Vitamina a y su incidencia en la agudeza visual en estudiantes del quinto y sexto curso de la Escuela Francisco Huerta Rendon Babahoyo Los Ríos, octubre 2019 febrero 2020. - Espinoza Bastidas, Diana Gabriela (2020)
Vitamin A deficiency leads to a decrease in visual acuity and in turn to a refractive error of the human eye that is known as ametropia and in recent years is a common problem in children, since vitamin intake deficiency and the use of electronic devices used at an early age by infants causes a decrease in vision and the necessary use of optical devices. The affectation of the visual acuity of children has to be determined in a technical way by the optometrist or ophthalmologist, who uses their scientific knowledge and necessary equipment to determine exactly what the level of visual deficit is, in order to find a solution Medical or optical. It is very important that children consume vitamins in their daily diet since they are necessary for physical development, within the vitamins that the child should consume is vitamin A, it is one that helps for visual development avoiding ametropias and pathologies such as Xerophthalmia which are disorders due to vitamin A deficiency and can be prevented by the systematic administration of retinol. In the absence of treatment xerophthalmia evolves very rapidly towards definitive blindness, between 250,000 and 500,000 children go blind every year due to a deficiency of vitamin A, for this reason the community should be motivated to increase vitamin A in the diet daily, especially in children and pregnant women.